Psychological changes among working-age adults with acquired vision impairment: The need for psychological intervention?. (January 2022) - Bassey, Emmanuel; Ellison, Caroline
This study investigates the psychological impacts of acquiring a vision impairment during working-age phase of adulthood and the potential negative effect on participation in community activities were highlighted. Adopting a qualitative and interpretive phenomenological approach, eight semi-structured in-depth interviews were conducted with eight adult users of vision rehabilitation services. Three broad themes were identified: (1) reduced participation in education, employment, and community activities, (2) feelings of hopelessness and depression from vision loss, and (3) psychological adjustment to vision loss over time. Findings are discussed in the context of the international literature, and recommendations that may enhance the vision rehabilitation services are made.